Towards the development of an appropriate organisational development approach for optimising the capacity building of community-based organisations (CBOs) : a case study of 3 CBOs in the Western Cape - Yachkaschi, Schirin (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (School of Public Management and Planning))—-Stellenbosch University, 2008.